Studi Kondisi Fisik dalam Olahraga Beladiri Tae Kwon-Do Dojang UNP - Yogi Setiawan; Vega Soniawan (Universitas Negeri Padang, 2021)
The problems in this research are: decreased achievement of Tae Kwon-Do Dojang athletes UNP. The purpose of this study was to determine the level of the physical condition of Tae Kwon-Do athletes. This type of research is descriptive research. The sample in this study amounted to 20 athletes. Instruments for testing aerobic endurance, endurance for arm muscle strength, leg muscle explosive power, and agility. The data analysis technique used descriptive statistics. The results of the analysis of the components of the Physical Condition of the Tae Kwon-Do Dojang Athlete UNP are as follows: (1) Aerobic Endurance Ability in the